2016
DOI: 10.1016/j.cmi.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Interest of [ 18 F]fluorodeoxyglucose positron emission tomography/computed tomography for the diagnosis of relapse in patients with spinal infection: a prospective study

Abstract: Relapse after treatment of a spinal infection is infrequent and difficult to diagnose. The aim of this study was to assess the diagnostic performance of [(18)F]fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in this setting. Thirty patients (21 men, nine women; median age 61.2 years) with a suspected spinal infection relapse were prospectively included between March 2010 and June 2013. The initial diagnosis of spinal infection was confirmed by positive bacterial cultures. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Previous study focusing mainly on hematogenous spinal infections found better diagnostic values than in our study [14,16,23,24]. Studies which assessed the diagnostic value of PET/CT in postoperative spinal infections found similar diagnostics values to those in our study [13,19]. De Winter et al found a sensitivity at 100% and a specificity at 81% for PET without CT.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous study focusing mainly on hematogenous spinal infections found better diagnostic values than in our study [14,16,23,24]. Studies which assessed the diagnostic value of PET/CT in postoperative spinal infections found similar diagnostics values to those in our study [13,19]. De Winter et al found a sensitivity at 100% and a specificity at 81% for PET without CT.…”
Section: Discussionsupporting
confidence: 79%
“…Lecture parameters of PET imaging were studied in a previous paper [13]. Briefly, suggestive signs of infection during PET/CT assessment included: (i) uptake location (linear or disciform uptake pattern in intervertebral disc space with/without involvement of endplates, bone involvement and/or surrounding soft tissue abscesses, involvement of arthrodesis material), (ii) uptake pattern (focal or multifocal, higher uptake in the side with suspected infection than in the contralateral side), (iii) uptake intensity estimated by the ratio of the maximum standardized uptake value (SUV max ) in the suspected foci over the SUV max of a considered normal region (for example adjacent disc without abnormality) with a ratio ≥2.3.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordant results were found in 6 of 56 patients for whom the MRI was positive, but the 18 F-FDG PET/CT did not reveal any lesions. In four of them, the diagnosis of spondylodiscitis was confirmed and false-negative 18 F-FDG PET/CT results were probably due to a weak infection characterized only by epidural involvement, whereas the low 18 F-FDG uptake may have been related to the different immune reaction caused by the various etiological agents [22,32,33]. In the remaining two patients, spondylodiscitis was finally not confirmed by follow-up and the false-positive MRI results were due to the presence of severe degenerative disc disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…Published data indicate that [ 18 F]FDG-PET/CT is superior to 67 Ga for the diagnosis of spinal infection and paraspinal soft tissue infection [82], and should be used in selected cases as an alternative to MRI [3,61,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109]. All studies in which a comparison between MRI and [ 18 F]FDG-PET/CT was performed have shown that a combination of the two techniques detects spinal infection in 100% of patients [102,110,111].…”
Section: Influence Of Medicationmentioning
confidence: 99%